2019
DOI: 10.2215/cjn.13131118
|View full text |Cite
|
Sign up to set email alerts
|

Association of Initiation of Maintenance Dialysis with Functional Status and Caregiver Burden

Abstract: Background and objectives Little is known about the functional course after initiating dialysis in elderly patients with ESKD. The aim of this study was to assess the association of the initiation of dialysis in an elderly population with functional status and caregiver burden. Design, setting, participants & measurements This study included participants aged $65 years with ESKD who were enrolled in the Geriatric Assessment in Older Patients Starting Dialysis study. All underwent a geriatric assessment and a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 45 publications
1
42
0
4
Order By: Relevance
“…It has recently been shown that a high proportion of patients will observe a decline in functional status in the first 6 months after initiating dialysis. In this study, the percentage of caregivers reporting a high burden of care increased from 23 to 38% after dialysis initiation [ 36 ]. In a study from our team, compared with autonomous PD patients, patients with nurse assistance had a lower risk of transfer to HD, while those with family assistance had a similar risk of transfer to HD.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that a high proportion of patients will observe a decline in functional status in the first 6 months after initiating dialysis. In this study, the percentage of caregivers reporting a high burden of care increased from 23 to 38% after dialysis initiation [ 36 ]. In a study from our team, compared with autonomous PD patients, patients with nurse assistance had a lower risk of transfer to HD, while those with family assistance had a similar risk of transfer to HD.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of frailty is higher among dialysis patients, and it increases with age: 44% of dialysis patients under 40 years are frail, while this prevalence reach 78% among dialysis patients above 70 years. In addition, functional decline is highly prevalent in older patients during the first 6 months of dialysis, especially in the presence of frailty (72). Patients with CKD (62) typically present many risk factors for frailty (71), such as anemia, osteoporosis, cardiovascular disease and chronic inflammation (72, 73).…”
Section: Frailty In Transplant Candidatesmentioning
confidence: 99%
“…In addition, functional decline is highly prevalent in older patients during the first 6 months of dialysis, especially in the presence of frailty (72). Patients with CKD (62) typically present many risk factors for frailty (71), such as anemia, osteoporosis, cardiovascular disease and chronic inflammation (72, 73). They also experience neuroendocrine changes, like 25-OH vitamin D deficiency, insulin-resistance (73) and low testosterone levels (74), commonly associated with frailty and sarcopenia (32).…”
Section: Frailty In Transplant Candidatesmentioning
confidence: 99%
“… 36 , 37 Our findings that higher predialysis physical health and fewer symptoms were associated with pre-emptive but not overall wait-listing may be related to the changes in HRQoL that many people experience after initiating dialysis. 38 Among those who report good physical health after starting dialysis, studies have shown higher rates of wait-listing, kidney transplantation. and posttransplantation survival.…”
Section: Discussionmentioning
confidence: 99%